The Impact of Rapid Left Ventricular Pacing during Pediatric Aortic Valvuloplasty on Postprocedural Aortic Insufficiency. (14th April 2016) - Ertugrul, Ilker; Karagoz, Tevfik; Celiker, Alpay; Alehan, Dursun; Ozer, Sema; Ozkutlu, Suheyla
Abstract: Objective: This study aims to determine efficacy and safety of rapid left ventricular pacing (RLVP) during balloon aortic valvuloplasty and effect on development of postprocedural aortic insufficiency (AI) in children. Design: This is a retrospective comparison of 56 children (mean age 18.3 month; 1 day–15 years of age) who underwent valvuloplasty by using RLVP with standard method (without pacing) during same time period (74 children; mean age 12.6 month; 1 day–18 years of age). Results: The systolic valvular gradient decreased from a mean 67 ± 20.4 mm Hg (26–120 mm Hg) before the procedure to a mean 27.6 ± 17.8 mm Hg (0–120 mm Hg) after the procedure. Procedure failed in two of the patients (3.6%) who received the RLVP; only two patients developed severe AI. Among those patients who underwent the standard method procedure failed in 6 patients (8.3%), whereas severe AI was seen in 15 (20.2%). RLVP decreased the incidence of postprocedure severe AI significantly ( P  < .01) but it had no effect on the gradient reduction of the procedure ( P  > .05). RLVP did not change the procedure duration, but decreased the duration of fluoroscopy significantly ( P  < .01). Conclusion: RLVP can be used effectively and safely for pacing during balloon aortic valvuloplasty procedures in all age groups; it decreases procedural failure rate, eases the procedure and prevents the development of AI through the stabilization of the balloon.